Harnessing the diversity of bacterial endophytes isolated from wild and cultivated taro plants against Phytophthora colocasiae - M. L. Jeeva; S. S. Veena; T. Makeshkumar; S. U. Shilpa; P. R. Amrutha; Tom Cyriac (JOURNAL OF ROOT CROPS, 2023)
Taro (Colocasia esculenta (L) Schott), a tuber crop which belongs to Araceae family is an important staple or subsistence crop for millions of people in developing countries. The crop capitulates to several fungal, bacterial, and viral diseases as well as some diseases of uncertain etiology. Taro leaf blight, a threatening disease of taro caused by Phytophthora colocasiae is associated with 90% and 50% loss in leaf and corm yield of taro, respectively. The preventive measures used by crop rotations and the use of improved disease resistant varieties have failed to completely eradicate the disease. Chemical fungicides are not only costly but have harmful effects on humans and the environment. Endophytes with antifungal activity can be exploited as excellent biocontrol agents against phytopathogenic fungi. Hence, this study was centred on evaluating the antagonistic activity of endophytic bacteria and fungi associated with wild and cultivar taro plants itself against Phytophthora colocasiae. The study involves isolation of endophytic bacteria and evaluation of antagonism against the pathogen using in vitro dual culture method. A total of 97 bacterial endophytes were isolated from taro plants and they were evaluated for their antagonistic activities against Phytophthora colocasiae. The in vitro study indicated that among the bacterial isolates, KV9 showed the highest antagonistic activity of 84.07±1.04%. This research study demonstrates that these endophytes can be exploited to create a promising biocontrol agent against P. colocasiae in the taro field.